(untitled) (World Conference on Agricultural and Earth Sciences, 2026)
This paper presents the results of assessing the health status of children and adolescents studying in various types of modern educational institutions, as well as the impact of indoor school environment factors on the educational process. The following environmental factors of the studied private and public schools wereanalyzed: humidity, temperature, air velocity, pressure, Formaldehyde HCHO (ug/m3), noise levels (db), and illumination in classrooms. An analysis wasconducted on optimizing indoor school factors, improving air quality, and enhancing the conditions for education and upbringing.